Penyuluhan Hukum Mengenai Bentuk-Bentuk Badan Usaha Bagi Usaha Mikro, Kecil, dan Menengah (UMKM) di Kelurahan Lembah Sari Kecamatan Rumbai Timur Kota Pekanbaru - Hasnati Hasnati; Sandra Dewi; Andrew Shandy Utama (Jurnal Pengabdian Multidisiplin, 2022)
The problem with partners in this community service activity is the people of Lembah Sari Village, Rumbai Timur District, Pekanbaru City regarding the forms of business entities for Micro, Small, and Medium Enterprises (MSMEs). The solution offered in this community service activity is to increase the knowledge of the people of Lembah Sari Village, Rumbai Timur District, Pekanbaru City regarding forms of business entities for Micro, Small and Medium Enterprises (MSMEs). The implementation method used in this community service activity is to use the lecture, dialogue, and discussion methods in order to provide legal counseling to the people of Lembah Sari Village. Participating partners in this community service activity are the Head of the Development and Community Empowerment Section of Lembah Sari Village and the Head of RW 07 Lembah Sari Village who participated in providing time, providing space, and supporting facilities, and presenting the community as activity participants. The output target of this community service activity is scientific articles published in national journals. The conclusion of this community service activity is that this activity has been successfully implemented and the benefits can be felt directly by the participants. Before the activity was carried out, of the 20 participants, only 19% answered correctly the material to be presented. Meanwhile, after the activity was carried out, 59% of participants answered that they had understood the material presented.